The inflammatory molecules IL-1β and HMGB1 can rapidly enhance focal seizure generation in a brain slice model of temporal lobe epilepsy - Chiavegato, Angela; Zurolo, Emanuele; Losi, Gabriele; Aronica, Eleonora; Carmignoto, Giorgio (Frontiers in Cellular Neuroscience, 2014)
Epilepsy is a neurological disorder characterized by a hyperexcitable brain tissue and unpredictable seizures, i.e., aberrant firing discharges in large neuronal populations. It is well established that proinflammatory cytokines, in addition to their canonical involvement in the immune response, have a crucial role in the mechanism of seizure generation. The purpose of the present study was to investigate the role of interleukin-1β (IL-1β) and high mobility group B1 (HMGB1) in the generation of seizure-like discharges using two models of focal epilepsy in a rat entorhinal cortex slice preparation. Seizure like-discharges were evoked by either slice perfusion with low Mg2+ and picrotoxin or with a double NMDA local stimulation in the presence of the proconvulsant 4-amino-pyridine. The effects of IL-1β or HMGB1 were evaluated by monitoring seizure discharge generation through laser scanning microscope imaging of Ca2+ signals from neurons and astrocytes. In the picrotoxin model, we revealed that both cytokines increased the mean frequency of spontaneous ictal-like discharges, whereas only IL-1β reduced the latency and prolonged the duration of the first ictal-like event. In the second model, a single NMDA pulse, per se ineffective, became successful when it was performed after IL-β or HMGB1 local applications. These findings demonstrate that both IL-1β and HMGB1 can rapidly lower focal ictal event threshold and strengthen the possibility that targeting these inflammatory pathways may represent an effective therapeutic strategy to prevent seizures.